Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Siswa Sekolah Dasar - Maisarah Maisarah; Muhammad Syarif (2022)
This study is related to the role of Islamic religious education teachers in guiding students to read and write the Qur'an at State Elementary School 27 Banda Aceh. The focus of the study was on the form of guidance for reading and writing the Koran for students during the Pandemic. The research subjects were the principal, Islamic religious education teacher, class teacher and Diniyah teacher. Data collection by interview, observation and documentation methods. Al-Qur'an reading and writing guidance at the State Elementary School 25 Banda Aceh is carried out by asking students to read the Qur'an every day before entering class hours. In addition, Diniyah teachers are also guided by using methods and media as well as encouraging and motivating. Materials related to the science of tajwid properly and correctly, reading the Qur'an properly and correctly in accordance with the rules of tajwid science, writing / khat basic hijaiyah / Arabic letters properly and correctly. There are positive changes shown by students, namely being able to read the Qur'an. This proves that even during the Covid-19 pandemic, and the learning process continues to run well and maximally by maintaining health protocols, of course, the success of fostering reading and writing the Qur'an also shows good and maximum success.